2015
DOI: 10.5194/acp-15-829-2015
|View full text |Cite
|
Sign up to set email alerts
|

Sunset–sunrise difference in solar occultation ozone measurements (SAGE II, HALOE, and ACE–FTS) and its relationship to tidal vertical winds

Abstract: Abstract. This paper contains a comprehensive investigation of the sunset-sunrise difference (SSD, i.e., the sunsetminus-sunrise value) of the ozone mixing ratio in the latitude range of 10 • S-10 • N. SSD values were determined from solar occultation measurements based on data obtained from the Stratospheric Aerosol and Gas Experiment (SAGE) II, the Halogen Occultation Experiment (HALOE), and the Atmospheric Chemistry Experiment-Fourier transform spectrometer (ACE-FTS). The SSD was negative at altitudes of 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 45 publications
(48 reference statements)
9
23
1
Order By: Relevance
“…Results from the regression depicting the mean diurnal variability present in each data set plotted as the percent difference between sunrise and sunset events. These results compare well with those of Sakazaki et al (2015).…”
Section: Diurnal Variabilitysupporting
confidence: 81%
See 1 more Smart Citation
“…Results from the regression depicting the mean diurnal variability present in each data set plotted as the percent difference between sunrise and sunset events. These results compare well with those of Sakazaki et al (2015).…”
Section: Diurnal Variabilitysupporting
confidence: 81%
“…Sakazaki et al (2015) used this method to analyze the diurnal variability present in SAGE II, HALOE, and ACE-FTS and found that not all data sets agree and the differences between SR and SS values differ typically by up to ∼ 5 %. The STS regression can extract the mean diurnal variability present in each data set and the results shown in Fig.…”
Section: Diurnal Variabilitymentioning
confidence: 99%
“…Past validation references for MLS O 3 include Jiang et al (2007), Froidevaux et al (2008a), and Livesey et al (2008), as well as the more recent work covering many satellite instruments by Hubert et al (2016). The original MLS data validation work for H 2 O is from Read et al (2007) and , who also described N 2 O validation; MLS HNO 3 validation was provided by Santee et al (2007). Based on Fig.…”
Section: Average Abundancesmentioning
confidence: 99%
“…The aforementioned NASA satellite ozone profile measurements have been shown to be in good agreement (∼ 5-10 %) between about 100 and 1 hPa (Cunnold et al, 1996;Tegtmeier et al, 2013;Froidevaux et al, 2008;Jiang et al, 2007;Livesey et al, 2008;Nazaryan and McCormick, 2005;Randall, 2003;Wang et al, 2002); around 1 hPa the diurnal cycle of ozone becomes prominent and local time sampling must be taken into account (Sakazaki et al, 2015). In contrast, water vapor retrievals from the various satellite instruments can exhibit biases of 20 % or more relative to one another, depending on the level, geographic location, and combination of instruments Hegglin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%